Use of near-infrared Raman spectroscopy to detect IgG and IgM antibodies against Toxoplasma gondii in serum samples of domestic cats - Duarte, J.; Pacheco, MTT; Machado, R. Z.; Silveira, L.; Zangaro, R. A.; Villaverde, A. B. (Cellular & Molecular Biology, 2002)
Near-infrared Raman spectroscopy (NIRS) is a particularly promising technique that is being used in recent years for many biomedical applications. Optical spectroscopy has gained increasing prominence as a tool for quantitative analysis of biological samples, clinical diagnostic, concentration measurements of blood metabolites and therapeutic drugs, and analysis of the chemical composition of human tissues. Toxoplasmosis is an important zoonosis in public health, and domestic cats are the most important transmitters of the disease. This disease can be detected by several serological tests, which usually have a high cost and require a long time. The goal of this work was to investigate a new method to diagnosis Toxoplasma gondii infections using NIRS. In order to confirm antibody detection, 24 cat blood scrum samples were analyzed by the Raman spectra, from which 23 presented positive serology to toxoplasmosis and one was a reference negative serum. Characteristic Raman peaks allowed differentiation between negative and positive sera, confirming the possibility of antibody detection by Raman spectroscopy. These results give the first evidence that this technique can be useful to quantify antibodies in cat sera.
Keywords: immunoglobulin; toxoplasmosis; Raman spectroscopy; Cat; near-infrared spectroscopy